Benzo[f]indole-4,9-dione Derivatives Effectively Inhibit the Growth of Triple-Negative Breast Cancer - Fabiana Sélos Guerra; Flaviana Rodrigues Fintelman Dias; Anna Claudia Cunha; Patricia Dias Fernandes (Molecules, 2021)
Triple-negative breast cancer (TNBC) is a subtype of breast cancer with poor clinical outcome, and currently no effective targeted therapies are available. Indole compounds have been shown to have potential antitumor activity against various cancer cells. In the present study, we found that new four benzo[f]indole-4,9-dione derivatives reduce TNBC cell viability by reactive oxygen species (ROS) accumulation stress in vitro. Further analyses showed that LACBio1, LACBio2, LACBio3 and LACBio4 exert cytotoxic effects on MDA-MB 231 cancer cell line by inducing the intrinsic apoptosis pathway, activating caspase 9 and Bax/Bcl-2 pathway in vitro. These results provide evidence that these new four benzo[f]indole-4,9-dione derivatives could be potential therapeutic agents against TNBC by promoting ROS stress-mediated apoptosis through intrinsic-pathway caspase activation.